Wombs for rent: Exploring the motivations behind Ghanaian Women’s decisions to become surrogate mothers - Isaac Mensah Boafo; Doris Ayeley Amarteifio; Peace Mamle Tetteh; Rosemond Akpene Hiadzi (PLoS ONE, 2026)
This study explores the motivations behind Ghanaian women’s decisions to engage in surrogacy, a growing practice within the country’s assisted reproductive technology landscape. Using a phenomenological qualitative approach, 21 surrogates from three privately owned agencies in Accra were interviewed to uncover the underlying factors influencing their choices. Thematic analysis, guided by Braun and Clarke’s framework, revealed three primary motivators: socio-economic factors, altruism, and religious beliefs. Financial incentives emerged as a significant driver, with participants citing surrogacy as a means to alleviate economic hardship, fund education, or support family needs. However, altruistic motivations were also prevalent, as some women expressed a deep empathy for childless couples and a desire to provide them with a sense of familial completeness. Religious motivations, rooted in Christian doctrines of love and service, further shaped the decisions of a subset of participants, who perceived surrogacy as a moral duty aligned with their faith. The findings underscore the complex interplay between economic vulnerability, cultural norms surrounding motherhood, and ethical considerations in shaping surrogacy decisions. The study situates these motivations within Ghana’s socio-economic context, highlighting how financial necessity intertwines with seemingly altruistic and religious frameworks. It concludes that while altruism and spirituality often surface as explicit motivations, economic realities play a critical underlying role, reflecting broader dynamics of commodification in global reproductive markets. This research contributes to a nuanced understanding of surrogacy in Ghana, providing insights into the ethical and socio-economic dimensions of this reproductive practice.